Propriedades farmacológicas das cascas de Himatanthus drasticus (Mart.) Plumel em modelos de analgesia, inflamação e cicatrização em camundongos - VIEIRA, Denilson Amorim (2012)
Himatanthus drasticus (Mart.) Plumel is popularly known in the North and Northeast Regions of Brazil as janaúba, janaguba, tiborna, jasmim-manga and pau-de-leite, as well. Brazilian traditional medicine knowledge attributes to the species antiinflammatory, analgesic, antitumoral and dewormer properties. Thus, the present study sought to investigate the anti-inflammatory, analgesic and wound-healing effects of the hidroalcoholic extract (HAE) made from Himatanthus dratiscus stem bark, which were collected in São Bento (MA) Brazil. Oral administration of HAE (0.5, 0.75 and 1.0 g/kg) reduced in a dose-dependent manner both oedema’s formation and leukocyte migration in mice submitted to intraplantar injection of 1% carragenin. Similarly, HAE also reduced the number of contortions in the acetic acid-induced writhing test. However, HAE had no effect on pain’s central perception. Corroborating these data, HAE showed significant wound-healing effect since it accelerated the wound contraction time in the mice. Finally, assessment of in vitro antioxidant activity of HAE suggested that phenolic compounds found in the extract is able to scavenger DPPH radical as fast as well-known antioxidants like -tocopherol. Therefore, this study shows that HAE promotes relevant analgesic, anti-inflammatory, woundhealing and antioxidant activity. Moreover, this study contributes to validation of popular use of the species as well as open up new perspectives for future investigations.